Managing Post-Hajj Relationships: Organizational Strategies of IPHI Semarang City - Sahara, Sa’adat Duta; Muhajarah, Kurnia (Jurnal Sosiologi Agama Indonesia (JSAI), 2026)
This study examines how IPHI Semarang City manages its relationship with hajj alumni after the pilgrimage through routine programs, local coordination, and community-based religious activities. The study addresses the question of how post-hajj ties are maintained once pilgrims return to everyday life and the intense social and spiritual atmosphere of the pilgrimage begins to fade. Using a qualitative case study design, data were collected through in-depth interviews, observation, and documentation. The primary data came from two organizational leaders and four hajj alumni who were actively involved in IPHI activities in Semarang. The data were analyzed through qualitative interpretation by focusing on recurring themes related to membership organization, religious activities, social programs, and efforts to sustain solidarity among former pilgrims. The findings show that IPHI Semarang City maintains post-hajj relationships through a set of structured organizational practices, including membership registration, majelis taklim, regular meetings, collaboration with local government, manasik haji, social donations, and an emerging Umrah savings program. These activities function as recurring points of contact that help preserve alumni ties, reinforce solidarity, and keep the social meaning of hajj active in community life. The study also finds that post-hajj solidarity does not continue automatically, but depends on repeated organizational interaction, local coordination, and shared spaces for religious and social engagement. At the same time, the continuity of these efforts is affected by practical limitations, especially the limited time of board members and the absence of a more formalized funding system.